Coupled thermal-hydraulic investigation on the heat extraction performance considering a fractal-like tree fracture network in a multilateral well enhanced geothermal system. (25th May 2022) - Zhang, Bo; Qu, Zhanqing; Guo, Tiankui; Sheng, Mao; Chen, Ming; Wang, Jiwei; Wang, Yunpeng; Guo, Chang
Highlights: A multi-lateral EGS model is constructed with a fractal-like tree fracture network. Effects of fracture geometric characteristics on heat extraction are studied. Effects of fracture heterogeneous characteristics on heat extraction are studied. Fracture optimization is suggested to improve the geothermal exploitation. Abstract: Due to their high conductivity, fractures play a vital role in geothermal exploitation. Previously, multiple random fractures, considered as the primary channel in enhanced geothermal systems (EGS), were studied extensively. However, natural fractures may not be developed in hot dry granite and fluid flow may be controlled by faults or hydraulic fractures. Based on fractal theory, this paper considers that hydraulic fractures have fractal-like tree characteristics and focuses on the influence of their geometric and heterogeneous characteristics on heat extraction. The results show that a higher fracture number, fracture length and a staggered fracture layout are the key factors affecting heat extraction, which obviously enhance the heat extraction efficiency. Additionally, a higher fracture length ratio and aperture ratio and a greater distance between the primary fracture and the lateral well are suggested in EGS, which are important factors influencing heat extraction. However, the effect is weaker than the above 3 factors. The fracture stage, the spacing between the primary fractures and the fracture angle are secondary factors, which should not be excessively focused on in EGS. The results can provide some reasonable suggestions for reservoir fracturing optimization.